OP12 Childhood Infectious Disease and Risk of Premature Death from Cancer: A Prospective Cohort Study. (17th September 2012) - Tennant, PWG; Parker, L; Thomas, JE; Craft, AW; Pearce, MS
Abstract : Background: The hygiene-hypothesis proposes that early-life infectious diseases may protect against a number of adverse health conditions later in life, most notably the development of cancer. Existing investigations of this association, however, have provided equivocal results, possibly due to inadequate adjustment for confounding or the use of retrospective exposure information. This study utilised longitudinal data from the Newcastle Thousand Families Study, a prospective cohort of 1147 individuals born in Newcastle-upon-Tyne (UK) in 1947, to assess the impact of various childhood infectious diseases on death from cancer between ages 15 and 60 years. Methods: Detailed information was collected prospectively at birth and during childhood on a number of early life factors. Episodes of illness during the first 15 years were obtained routinely by health visitors, who regularly visited the participants' homes, or directly from the family doctor or hospital. All study members were 'flagged' by the UK National Health Service Central Register when they died or emigrated. Deaths from cancer between ages 15 to 60 years were analysed in relation to childhood infections, adjusting for potential early-life confounders, using Cox proportional-hazards regression. Results: Of the 1060 study members known to be alive at age 15 years, 88 died before aged 60 years, including 37 from cancer – the leading cause of death. Childhood history of measles and childhood history of influenza, were both independently associated with a lower risk of death from cancer during ages 15 to 60 years (influenza: adjusted hazard ratio, aHR=0.39, 95% CI: 0.17–0.88, p=0.03; measles: aHR=0.49, 95% CI: 0.24–0.98, p=0.04). In contrast, childhood history of whooping cough was associated with a higher risk of death from cancer during ages 15 to 60 years (adjusted HR, aHR=4.88, 95% CI: 2.29–10.39, p<0.0001). The association between whooping cough and cancer-related mortality was borderline significantly different between men and women (p=0.05), with a stronger association among women than men (women: aHR=12.20, 95% CI: 3.01–49.42, p=0.0005; men: aHR=2.10, 95% CI: 0.80–5.50, p=0.13). Conclusion: In a pre-vaccination cohort from the North of England, childhood infection with measles and influenza were associated with a reduced risk of death from cancer in adulthood, while childhood whooping cough was associated with an increased risk. These results suggest that there may be some disease-specific associations between childhood infectious diseases and death from adult cancer, however further studies are required to confirm the specific associations identified.